INFLUENCE OF CSR ACTIVITY, SERVICE QUALITY AND BRAND ATTITUDE TO CUSTOMER’S RE-VISIT INTENTION IN HOTEL INDUSTRY - Elferdy; Fariza Astrini; Ira Chandra Tio; Prayitno Susanto; Simarmata, Barita Martin Parluhutan; Budi Utomo (The Islamic Education and Multiculturalism Foundation, 2022)
Abstract: Hotels are a key component of tourism industry and tourism industry is strongly reliant on them. The tourism industry and the hotel sector are most closely related. Corporate social responsibility is a key strategic resource in the hospitality sector. This study intends to investigate probable causes of guests' favorable opinions of hotel. The suggested approach covers environmental CSR, charitable CSR, physical quality, employee behavior, customer satisfaction, brand attitude, and revisit intention. Using samples of domestic and international hotel guests who visited Bali, Indonesia, the model is put to the test. Testing of the model made in this study resulted in customers satisfaction and revisit intention positively influenced by CSR philanthropy. According to hypothesis testing, Environmental and Philanthropy CSR are more important to hotel guests' satisfaction and revisit intention than service quality and brand attitude. Purpose – CSR is regarded as a valuable resource, especially in the service industry. Only a few research have looked at the combined effects of brand attitude and service quality, in contrast to earlier research that concentrated on CSR activities and service quality. Therefore, the goal of this study is to investigate the possible reasons for hotel customers' positive perceptions of the establishment. Design/methodology/approach –The suggested model considers CSR efforts, service encounters, customer happiness, brand attitude, and intention to return. Samples of Indonesian and foreign hotel clients are used to test the model. In tests of the proposed model, path coefficients from CSR activities (environmental and philanthropic), but not from physical quality, staff behavior, and brand attitude provide meaningful results. Findings – According to hypothesis testing, perceived environmental and philanthropy CSR support are more important to customer satisfaction and intent to return than physical quality, employee behavior, and brand attitude. From these findings, it shows that hotels need to make better CSR strategies, especially in CSR philanthropy. CSR can be a good marketing tool to